2008
DOI: 10.1177/0271121408324447
|View full text |Cite
|
Sign up to set email alerts
|

Do Variables Associated With Quality Child Care Programs Predict the Inclusion of Children With Disabilities?

Abstract: Little research has been carried out on the inclusion of children with special needs in child care. The purpose of this study was to determine what variables predict the inclusion of children with disabilities in centers and home care. Logistic regression was used to examine the association of several indicators of quality child care and inclusion. For directors, teachers, and home care providers, the strongest predictor was having taken a course on working with children with disabilities. Larger centers and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 29 publications
0
24
1
3
Order By: Relevance
“…In fact, one study suggests that the most prevalent barrier to inclusive childcare is lack of knowledge regarding care requirements of children with special needs (Dinnebeil, McInemey, Fox, & Juchartz-Pendry, 1998). Training surrounding the care of children with disabilities is a predictor of the quality of inclusive childcare environments (Essa et al, 2008). In Canada, training requirements vary by province but may not require experience working with children with disabilities or on facilitating inclusion (Irwin, Lero, & Brophy, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, one study suggests that the most prevalent barrier to inclusive childcare is lack of knowledge regarding care requirements of children with special needs (Dinnebeil, McInemey, Fox, & Juchartz-Pendry, 1998). Training surrounding the care of children with disabilities is a predictor of the quality of inclusive childcare environments (Essa et al, 2008). In Canada, training requirements vary by province but may not require experience working with children with disabilities or on facilitating inclusion (Irwin, Lero, & Brophy, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences in the number of childcare arrangements between children with EOD and typically developing children. In slight contrast to other research (Essa et al,2008;Rosenzweig et al, 2008), Booth-LaForce & Kelly (2004) found that the most common type of childcare that children with EOD received was non-parental relative care, that is to say, for example care by a grandparent. The second most common form of care was provided by the father's/mother's partner.…”
Section: Outcomes Associated With Childcarecontrasting
confidence: 64%
“…For example previous studies (Essa et al, 2008) have found that children with differences were more likely to attend childcare that was larger in size, such as centre care. Yet other research suggested that children with disabilities received the least amount of childcare in a professional childcare setting such as centres or preschool (Rosenzweig et al, 2008).…”
Section: Types Of Childcarementioning
confidence: 99%
“…Furthermore, teachers are encouraged to recognize and leverage the links among academic and non-academic learning areas, with the final aim of fostering children’s holistic development. In summary, both the NEL and the Guide fully embrace a Western constructivist epistemological perspective (Essa and Burnham, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%